2019
DOI: 10.1111/cei.13255
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapies based on PD-1/PD-L1 pathway inhibitors in ovarian cancer treatment

Abstract: Summary Immunotherapies based on anti‐programmed death 1/programmed death ligand 1 (PD‐1/PD‐L1) pathway inhibitors may turn out effective in ovarian cancer (OC) treatment. They can be used in combination with standard therapy and are especially promising in recurrent and platinum‐resistant OC. There is growing evidence that the mechanism of the PD‐1/PD‐L1 pathway can be specific for a particular histological cancer type. Interestingly, the data have shown that the PD‐1/PD‐L1 pathway blockade may be effective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 80 publications
0
37
0
Order By: Relevance
“…Early diagnosis improves survival, but only 15% of OC cases are diagnosed at an early or localized stage. OC therefore presents a significant threat to the health of women worldwide ( 1 , 2 ). Although there are numerous chemotherapeutics available to treat OC and improve patient prognosis, the chemoresistance of OC remains a major obstacle for the successful treatment of OC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis improves survival, but only 15% of OC cases are diagnosed at an early or localized stage. OC therefore presents a significant threat to the health of women worldwide ( 1 , 2 ). Although there are numerous chemotherapeutics available to treat OC and improve patient prognosis, the chemoresistance of OC remains a major obstacle for the successful treatment of OC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells escape T-cell-mediated cellular cytotoxicity through regulating the programmed cell death (Pd)-1/Pd-ligand 1 (Pd-l1) pathway (26). Targeting the Pd-1/Pd-l1 pathway has emerged as a novel strategy in the treatment for a variety of malignancies (27)(28)(29). a previous study suggested that mir-140 exerts anti-osteosarcoma efficacy via targeting the immune checkpoint molecule Pd-l1 (30).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, mAbs are currently in clinical trials, including Phase III, both in single and combined therapy. [34][35][36][37] Unfortunately, treatment based on mAbs inhibiting the PD-1/PD-L1 pathway is only efficient in a small group of OC patients. Moreover, OC treatment results are not as satisfying as in the case of other solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to find predictive markers and understand the OC microenvironment to implement the treatment for precise groups of OC patients. 8,11,19,33,34 What is interesting, blood-borne metastases are rare in OC. The most common mechanism of metastasis is the release of cells into the peritoneal cavity from the primary tumor.…”
Section: Discussionmentioning
confidence: 99%